Activation of the P2X7 receptor in the dental pulp tissue contributes to the pain in rats with acute pulpitis. (23rd June 2022) - Xiao, Zhi; Xu, Min; Lan, Lan; Xu, Ke; Zhang, Yue-Rong
Treatment of acute pulpitis (AP) is beneficial for pain relief and pulp regeneration. The purinergic P2X7 receptor activation is responsible for the formation and maintenance of inflammation and pain. This study aims to determine the role of the pulp tissue P2X7 receptor to activate the mechanisms of the AP in rats. The Sprague-Dawley rats were divided into groups, namely, normal, normal saline (NS), and lipopolysaccharide (LPS) groups. Alterations in pain behavior were detected through head-withdrawal thresholds (HWTs), and the pathological changes in pulp tissue were studied through hematoxylin and eosin staining. The expression of the P2X7 receptor in pulp tissue was observed through immunohistochemistry and Western Blotting. The effect of the P2X7 receptor antagonist A-740003 on HWTs was also observed. The levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in the pulp tissue of rats were analyzed through enzyme-linked immunosorbent assay. The HWTs were reduced in the rats with AP. Inflammation is formed but was found more severe in the LPS group than the NS group, and the expression levels of the P2X7 receptors in the NS and LPS groups were higher than in the normal group. The periodontal ligament injection of the A-740003 dose-dependant increases the HWTs in rats with AP. The IL-6 and TNF-α levels in the pulp in the NS and LPS groups were increased but reversed by A-740003 injection. In rats with AP, the expression level of the P2X7 receptor and IL-6/TNF-α release was upregulated. The A-740003 can relieve pain and reduce the inflammation progression in rats with AP.